The effect of strength and speed training program in speed of female soccer players - Papadopoulou, Z.; Bekris, E.; Manolopoulos, E.; Komsis, G.; Ispyrlidis, I.; Komsis, S.; Gkisis, I. (Global journal for research analysis, 2017)
Female soccer is a popular team sport, which is characterized by the requirements of the technical features, and high tness level of the players. Few studies have been describing requirements in female Soccer regarding the physical requirements. The aim of this study was to investigate the e?ect in speed improvement of female soccer players after the implementation of a specic strength and speed training program. The sample of the research was 20 female soccer players without injury problems. They were randomly divided into experimental (EG, n = 10) and control group (CG, n = 10). Measurements of 10m acceleration, 10m flying start and 30m maximum speed were carried out at the beginning and after the implementation of the 6-week power and speed training program. Speed and acceleration measured by photocells fences (Autonics Beam Sensor BL5M - MFR) and a digital timer (Saint Wien Digital Timer Type H5K. To test the effect of the program and identify statistically signicant differences in the individual dependent variables between measurements (before and after) we used two-way analysis of variance (two wayAnova) with repeated measures (REPEATED MEASURES) the second factor (2X2). After analyzing the interaction followed independent analyzes of samples t-test and paired t-test. For this purpose we used the statistical package SPSS 18.0 and signicance level will be set to p <0.05. In all variables we found a statistically signicant interaction between groups and repeated measurements of the experimental group and the control group Followed by paired t test (paired t test) and found signicant differences in the following variables (been adjusted Bonferroni) t10m, t10mmax t30m. Speed is an important factor in the selection of talent in development groups, and for this reason must be contained in the design of training programs.